2020
DOI: 10.1002/bio.3979
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrochemiluminescence of Ru(bpy)32+‐doped silica nanoparticles by chitosan/Nafion shell@carbon nanotube core‐modified electrode

Abstract: Although Ru(bpy)32+‐doped silica nanoparticles have been widely explored as the labelling tags for electrochemiluminescence (ECL) sensing different targets, the poor electrical conductive properties of the silica nano‐matrix greatly limit their ECL sensitivity. Therefore, a novel scheme to overcome this drawback on Ru(bpy)32+‐doped silica nanoparticles ECL is desirable. Here, a new scheme for this purpose was developed based on electrochemically depositing a nanoscale chitosan hydrogel layer on the carbon nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…From the CV curves of the chitosan/Nafion/MWNTs-modified electrode (Figure S3c), the redox peak current of the Fe(CN strengthening the affinities with each other. [33] Therefore, the elec- corresponding CV responses of different modified electrodes were also improved (Figure 4). The above experimental results showed that the chitosan/Nafion/MWNTs-modified electrode was an excellent ECL immunosensing platform, while the Ru(bpy) 3 2+ /chitosan/SiO 2 NPs were suitable as electroactive labels for high sensitivity detection of PSA in the proposed ECL immunosensor.…”
Section: +mentioning
confidence: 91%
“…From the CV curves of the chitosan/Nafion/MWNTs-modified electrode (Figure S3c), the redox peak current of the Fe(CN strengthening the affinities with each other. [33] Therefore, the elec- corresponding CV responses of different modified electrodes were also improved (Figure 4). The above experimental results showed that the chitosan/Nafion/MWNTs-modified electrode was an excellent ECL immunosensing platform, while the Ru(bpy) 3 2+ /chitosan/SiO 2 NPs were suitable as electroactive labels for high sensitivity detection of PSA in the proposed ECL immunosensor.…”
Section: +mentioning
confidence: 91%
“…It is best suited for coating of a small and defined area, because for larger areas, controlling thickness, porosity, and uniformity of the film is more difficult [34]. The general process includes the mixing of recognition elements such as enzymes [8,9,35,36], DNA derivatives [10,37], or probes such as fluorescent dyes, luminophores [38], or nanoparticles [39,40] with an evaporable solvent and a binder (e.g., hydrogels, polymers, or cross-linkers like glutaraldehyde), followed by application of this cocktail to the desired surface. In addition to the cocktail composition and surface conditions, drying time, annealing temperature, and the applied volume are contributing factors toward the final homogeneity and morphology of the deposited material.…”
Section: Drop Coatingmentioning
confidence: 99%
“…Carbon nanomaterials for miRNA detection can be in the form of carbon nanoparticles [ 31 ], carbon nanotubes [ 32 ], nanofibers [ 33 ], quantum dots [ 34 ], fullerenes [ 35 ], graphene nanosheets [ 36 ], and graphene oxide [ 37 ].…”
Section: Nanomaterials Used As Substratesmentioning
confidence: 99%